Eye Involvement as the Initial Sign of Multiple Sclerosis in a Case with Familial Mediterranean Fever - Neslihan Sevimli; Remzi Karadag; Bahri Aydin; Müferret Ergüven; Hüseyin Bayramlar (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2015)
Familial Mediterranean fever (FMF) is a common hereditary auto-inflammatory disease characterized by recurrent and selflimited attacks of serosal inflammation. The disease demonstrates an autosomal recessive inheritance pattern. Serositis can be observed as abdominal pain (peritonitis), chest pain (pleuritis) and joint pain (arthritis) usually accompanied by fever. The disease is more prevalent among the people living in the Middle East and Mediterranean regions. The prevalence ranges from 1/250 to 1/1000 depending upon the geographic locations [1]. Reports of ophthalmological manifestations in FMF are few and include retinal changes, panuveitis, anterior uveitis, scleritis, and episcleritis [2]. Multiple Sclerosis (MS) is a disease of the central nervous system characterized by multiple areas of inflammation and demyelination in the white matter of the brain and spinal cord [3]. Common neuro-ophthalmologic manifestation of MS is unilateral and painful vision loss due to optic neuritis. This is the first manifestation of MS, and usually appears as single-sided retrobulbar optic neuritis. Ocular motor deficits in multiple sclerosis include inter nuclear ophthalmoplegia (INO) and nystagmus, resulting in diplopia, oscillopsia, blurred vision, loss of stereopsis, and reading fatigue [3].